Automation, performance and international competition: a firm-level comparison of process innovation. (5th July 2020) - Kromann, Lene; Sørensen, Anders
SUMMARY: The automation of production processes is an important topic on the policy agenda in high-wage countries, and Denmark is no exception. However, the knowledge of the adoption of automation technologies across firms, of drivers of investments in automation, and on the association between automation and firm performance are limited. This paper uses a new survey to collect data on automation combined with register data to examine these issues. The variation in the adoption of automation technologies is high but the change in adoption over time is slow, and almost half of Danish manufacturing firms relied greatly on manual production processes in 2010. Increasing international competition from China is a driver for investments in automation, i.e. the manufacturing firms that are exposed to intensifying competition from China in their output markets invest more in automation than firms that are not exposed to this type of competition. We conduct external validation of the automation survey by examining the association between the automation measures and firm performance measures constructed from completely independent data sources. We find that the measures of automation are significantly associated with productivity and profitability.